Computational Study of Transition State of [1,2,5]-Thiadiazolo- [3,4-C]-benzoxadiazole-1-oxide and 3-Oxide with ab initio Methods - Rezaei Sameti, Mahdi (Asian Journal of Chemistry, 2010)
ab initio and density functional calculations are used to analyze the transition state optimization and estimating reaction barriers and rate constant of transition state for exchanging oxygen in [1,2,5]-thiadiazolo- [3,4-C]-benzoxadiazole-1-oxide and 3-oxide. All species have been optimized utilizing Gaussian 98 procedure package at the RHF/6-31++G, RHF/6-31++G**, RHF/6-311++G**, B3LYP/6-31++G, B3LYP/6- 31G** computational levels. The vibrational mode analysis is used to elucidate the relationships of transition states, intermediates and products. The procedures for finding optimization and verification of transition state structure is quite straightforward and concise. The extensive investigation shows that the reaction mechanism is reliable.